Local criteria for the selection of wild food plants for consumption and sale in Alagoas, Brazil - Lins Gomes, Danúbia; dos Santos Ferreira, Rita Paula; da Costa Santos, Élida Monique; Vasconcelos da Silva, Rafael Ricardo; Medeiros, Patrícia Muniz (Ethnobiology and Conservation, 2020)
Understanding the reasons for the consumption of certain plant resources instead of others has important implications for biological conservation. This study aimed to answer the following question: What are the factors that determine the consumption and perceived commercial potential of certain wild fruit species among extractivists from two rural communities in northeastern Brazil? This study developed a participatory approach to identify the fruit species known and/or used by extractivists. The selected species were presented to the extractivists using semi-structured interviews. A Likert scale (from 1 to 5) was used by interviewees to assign scores to 17 wild fruits in terms of local consumption, commercial potential, taste, nutritional potential, adverse effects, post-harvest durability, additional uses, temporal availability (fruit), spatial availability (fruit), spatial availability (plant), ease of collection, and ease of cultivation. Multiple regression analysis was performed to show the variables that best explained the selection of plants for consumption and sale. The results showed that only taste determined the commercial potential of plants, while taste and nutritional potential were the variables that best explained domestic consumption. In contexts in which edible wild plants do not form the base of the local diet, taste may be more relevant in relation to other variables such as availability and nutritional potential.